ANALISIS PENGUASAAN KETERAMPILAN MENGAJAR MAHASISWA PLP PROGRAM STUDI PENDIDIKAN FISIKA, UNIVERSITAS RIAU - Mailaff Maulidya Cahyani; Shofiyatum Mujahidah (Jurnal Pendidikan, 2023)
Teaching skills are skills that must be mastered by every teacher or prospective teacher. This study aims to determine the level of mastery of teaching skills for PLP students in physics education at the University of Riau. The teaching skills seen are; 1) skills in opening lessons, 20 skills in conveying learning objectives, 3) skills in conveying learning material, 4) skills in mastering teaching materials while delivering material 5) skills in class management during learning takes place, 6) skills in conformity evaluation with the material presented, and 7) closing skills. This study uses a quantitative research method with a descriptive approach method. The results of this study are that the teaching skills of PLP physics education students get a score of 63.1% in the good category. So that it can be said that PLP physics education students have mastered several teaching skills well.